Statistical optimization of physicochemical factors for lignin peroxidase production using pome as substrate - Alam, Md. Zahangir; Abdul Karim, Mohamed Ismail; Mespuan, M T (2006)
A laboratory-scale lignin peroxidase (LiP) or ligninase production from palm oil mill effluent (POME) by Phanerochaete chrysosporium in liquid state bioconversion (LSB) was studied. The effect of the concentration of substrate and co-substrate, inoculum size, initial pH of the medium, and the agitation speed were observed for maximum production of LiP. The statistical optimization of the physicochemical conditions by polynomial regression model through the effect of linear, quadratic and polynomial interaction were carried out for the enzyme production. The experimental design and optimization was done by using the fractional factorial design formulated by a statistical optimization software MINITAB. The lignin peroxidase activity was observed periodically by the enzyme assaying and other responses such as COD, TSS, as well as reducing sugar determination. The results showed that temperature of 40°C, substrate concentration of 2%, co-substrate concentration of 2%, pH 6, inoculum size of 2%, and agitation of 250 rpm maximize the LiP production in liquid state bioconversion of POME.